A Cr3C2 ceramic-reinforced composite powder for arc spraying, an iron-based amorphous composite coating, and their preparation method.

CN122913495APending Publication Date: 2026-10-16HENAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611118810.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]为了解决现有技术中非晶合金基体与陶瓷相界面相容性差、涂层孔隙率高的问题,本发明提供一种用于电弧喷涂的Cr3C2陶瓷增强复合粉末、铁基非晶复合涂层及其制备方法

Benefits of technology

本发明采用铁基非晶形成成分(Fe-B-Si-Nb)与碳化铬复合作为用于电弧喷涂制备涂层的原料,能够解决制备涂层时,非晶合金基体与Cr3C2陶瓷相界面相容性差、涂层孔隙率高的问题。其中,B和Si主要通过降低合金熔点、提高熔体流动性和润湿性,使熔融金属在喷涂过程中能够更好地包覆陶瓷颗粒,从而改善陶瓷相与基体之间的界面结合状态,减少孔隙的形成。Nb元素可降低原子扩散速率,提高晶化激活能,从而抑制晶化过程。同时,Nb有助于稳定非晶结构,使陶瓷相在基体中均匀分布而不破坏整体结构连续性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122913495A_ABST
    Figure CN122913495A_ABST
Patent Text Reader

Abstract

A kind of Cr3C2 ceramic reinforced composite powder for arc spraying, iron-based amorphous composite coating and preparation method thereof, it relates to the field of material surface engineering, the composite powder is made by Fe-B-Si-Nb iron-based amorphous alloy powder and Cr3C2 ceramic powder mixing;With the total mass of composite powder, the mass fraction of Cr3C2 ceramic powder is 5%-8%;The preparation method of iron-based amorphous composite coating includes the following steps, selects low carbon steel belt as cladding skin, fills Cr3C2 ceramic reinforced composite powder to the inside of steel belt, after filling, is sequentially rolled, draws processing, and the powder core wire is prepared;With powder core wire as spraying raw material, after arc spraying on the surface of metal matrix, it is cooled naturally, and the iron-based amorphous composite coating is obtained;The present application uses iron-based amorphous forming component (Fe-B-Si-Nb) and chromium carbide composite as raw material for arc spraying preparation coating, can improve the interface bonding state between amorphous alloy matrix and Cr3C2 ceramic phase, and reduce the porosity of coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials surface engineering, specifically to a Cr3C2 ceramic-reinforced composite powder for arc spraying, an iron-based amorphous composite coating, and a method for preparing the same. Background Technology

[0002] Thermally sprayed cermet coatings possess excellent wear resistance, corrosion resistance, and high-temperature resistance, and are widely used in many industrial fields such as machinery manufacturing, metallurgy, energy, and aerospace. The overall service performance of cermet coatings mainly depends on the hard ceramic reinforcing phase and the metal matrix supporting the ceramic phase. The compatibility and interfacial bonding state between the hard ceramic reinforcing phase and the metal matrix are important factors affecting the coating quality.

[0003] Currently, Fe-based, Ni-based, and Co-based crystalline alloys are widely used in industry as substrates for cermet coatings. These materials have well-designed compositions, good compatibility with various spraying processes, and have achieved large-scale application. However, crystalline alloys themselves have inherent defects. The matrix inevitably contains discontinuous regions such as grain boundaries, dislocations, and compositional segregation. These defects are difficult to eliminate using conventional spraying processes and easily become stress concentration sources, inducing coating crack initiation and accelerating the penetration of corrosive media. Therefore, the performance improvement potential of traditional crystalline alloy-based cermet coatings is limited, and they cannot meet the harsh operating conditions of heavy loads, high speeds, strong wear, and long service cycles of high-end equipment components.

[0004] Compared to crystalline alloys, amorphous alloys, also known as metallic glasses, possess a homogeneous microstructure with long-range disorder and no grain boundaries, theoretically providing an ideal continuous support matrix for ceramic reinforcing phases. However, existing amorphous composite coatings still face several key technical challenges: poor interfacial compatibility between the amorphous matrix and the ceramic reinforcing phase, insufficient lattice matching, and the tendency of the hard ceramic phase to induce crystallization transformation in the amorphous matrix under the thermal effects of spraying, resulting in coatings with generally high porosity, which greatly limits the research and engineering application of high-performance amorphous composite coatings. This is especially true for arc spraying processes, where the droplet velocity is low and the cooling rate is only 10⁻⁶. 3 ~10 5 K / s, and maintaining the stable preservation of the amorphous structure requires a high cooling rate. Due to this constraint, it is difficult to prepare metal-ceramic coatings with high amorphous content and dense structure by relying on conventional arc spraying processes. Summary of the Invention

[0005] To address the problems of poor compatibility between amorphous alloy substrates and ceramic phases and high coating porosity in existing technologies, this invention provides a Cr3C2 ceramic-reinforced composite powder for arc spraying, an iron-based amorphous composite coating, and a method for preparing the same.

[0006] To achieve the above objectives, the specific solution adopted by the present invention is as follows: a Cr3C2 ceramic reinforced composite powder for arc spraying, which is made by mixing Fe-B-Si-Nb iron-based amorphous alloy powder with Cr3C2 ceramic powder; the mass fraction of Cr3C2 ceramic powder is 5% to 8% based on the total mass of the composite powder.

[0007] As a further optimization of the above technical solution, the Fe-B-Si-Nb iron-based amorphous alloy powder is composed of the following components by mass percentage: B 2~8%, Si 2~6%, Nb 2~10%, and the balance Fe and unavoidable impurity elements.

[0008] As a further optimization of the above technical solution, the particle size of Fe-B-Si-Nb iron-based amorphous alloy powder is 5-100 μm; the particle size of Cr3C2 ceramic powder is 5-100 μm.

[0009] A method for preparing an iron-based amorphous composite coating includes the following steps: selecting a low-carbon steel strip as the outer sheath, filling the steel strip with Cr3C2 ceramic-reinforced composite powder, and after filling, sequentially rolling and drawing to obtain a powder core wire; using the powder core wire as the spraying raw material, applying it to the surface of a metal substrate by arc spraying and then allowing it to cool naturally to obtain the iron-based amorphous composite coating; wherein, the process parameters for arc spraying are: spraying voltage 28-32 V, spraying current 140-160 A, spraying distance 90-110 mm, and spray gun moving speed 25-35 m / min.

[0010] As a further optimization of the above technical solution, the process parameters for arc spraying are: spraying voltage 30V, spraying current 150A, spraying distance 100mm, and spray gun moving speed 30m / min.

[0011] As a further optimization of the above technical solution, the diameter of the core filament is 1.9~2.1mm, and the thickness of the outer sheath is 0.15-0.25mm.

[0012] As a further optimization of the above technical solution, the metal matrix is ​​a 45 steel matrix.

[0013] As a further optimization of the above technical solution, the metal substrate surface is subjected to rust removal, degreasing, and sandblasting roughening treatment in sequence before being coated with electric arc spraying.

[0014] As a further optimization of the above technical solution, the coating on the surface of the workpiece after natural cooling is ground and polished to obtain the iron-based amorphous composite coating.

[0015] An iron-based amorphous composite coating prepared by the method described above.

[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention employs a composite of iron-based amorphous forming elements (Fe-B-Si-Nb) and chromium carbide as a raw material for arc spraying coatings. This addresses the problems of poor interfacial compatibility between the amorphous alloy matrix and the Cr3C2 ceramic phase, and high coating porosity during coating preparation. B and Si primarily improve the alloy's melting point and enhance melt flowability and wettability, allowing the molten metal to better coat ceramic particles during spraying. This improves the interfacial bonding between the ceramic phase and the matrix, reducing porosity. Nb reduces the atomic diffusion rate and increases the crystallization activation energy, thereby inhibiting the crystallization process. Simultaneously, Nb helps stabilize the amorphous structure, ensuring a uniform distribution of the ceramic phase within the matrix without disrupting the overall structural continuity.

[0017] Arc spraying processes suffer from low particle velocity and limited cooling rates, while the stable retention of amorphous phases requires a high cooling rate. This invention uses a composite powder composed of Fe-B-Si-Nb iron-based amorphous alloy powder with a Cr3C2 ceramic phase to effectively strengthen and reduce coating porosity under existing arc spraying cooling conditions, based on a certain amorphous ratio. This breakthrough overcomes the technical limitations of arc spraying in the preparation of amorphous coatings. In the alloy system, B and Si elements can enhance the glass-forming ability of the alloy, while Nb elements can increase the crystallization activation energy and inhibit atomic diffusion. At the same time, the introduced Cr3C2 ceramic particles can regulate element diffusion, grain growth, and local heat dissipation behavior of molten droplets. During the arc spraying thermal cycle, some Cr3C2 may undergo carbon diffusion and phase transformation to form Cr-C type hard second phases represented by Cr3C2 and Cr7C3, which improve the coating's load-bearing capacity through dispersion strengthening. Meanwhile, the ceramic second phase can promote microstructure densification and improve the overall performance of the coating, ultimately forming an iron-based amorphous composite coating with an amorphous phase as the main body and Cr-C type hard phases dispersedly distributed. Attached Figure Description

[0018] Figure 1 The microhardness of the FeBSiNb-Cr3C2 coating along the cross-sectional direction; Figure 2 XRD test results for the FeBSiNb-Cr3C2 coating; Figure 3 The microscopic cross-sectional morphology of the FeBSiNb-Cr3C2 coating and the substrate; Figure 4 The cross-sectional morphology (a) and compositional analysis results (b) of the FeBSiNb-Cr3C2 coating are shown. Figure 5 The EDS surface scan region of the FeBSiNb-Cr3C2 cross section; Figure 6 EDS surface scan results for the FeBSiNb-Cr3C2 cross section; Figure 7 Three-dimensional morphology and surface contour of FeBSiNb-Cr3C2 coating surface; Figure 8 The coefficient of friction for the FeBSiNb-Cr3C2 sample; Figure 9 SEM image of FeBSiNb powder before spraying; Figure 10 SEM image of FeBSiNb-Cr3C2 powder before spraying; Figure 11 XRD patterns of FeBSiNb (Comparative Example 1) and FeBSiNb-Cr3C2 (Example 1) powders before spraying; Figure 12 XRD patterns of FeBSiNb (Comparative Example 1) and FeBSiNb-Cr3C2 (Example 1) amorphous coatings; Figure 13 (a) is FeBSiNb (Comparative Example 1). Figure 13 (b) is a transmission electron microscope image of FeBSiNb-Cr3C2 (Example 1); Figure 14 This is a schematic diagram of the preparation method of the present invention. Detailed Implementation

[0019] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. Parts not described or disclosed in detail in the following embodiments of the present invention should be understood as prior art known or should be known by those skilled in the art.

[0020] This invention discloses a Cr3C2 ceramic-reinforced composite powder for arc spraying, which is prepared by mixing Fe-B-Si-Nb iron-based amorphous alloy powder and Cr3C2 ceramic powder; the mass fraction of Cr3C2 ceramic powder is 5% to 8% based on the total mass of the composite powder. The Fe-B-Si-Nb iron-based amorphous alloy powder, by mass percentage, contains 2-8% B, 2-6% Si, 2-10% Nb, and the balance being Fe and unavoidable impurity elements; the particle size of the Fe-B-Si-Nb iron-based amorphous alloy powder is 5-100 μm; the particle size of the Cr3C2 ceramic powder is 5-100 μm.

[0021] This invention also discloses a method for preparing an iron-based amorphous composite coating, comprising the following steps: 1. Preparation of Powder-Core Wire: Low-carbon steel strip is used as the outer sheath, filled with a proportionally mixed mixture of Fe-B-Si-Nb iron-based amorphous alloy powder and Cr3C2 ceramic powder, and then rolled and drawn to produce powder-core wire. The amount of ceramic powder is controlled to be 5%-8% of the total wire mass. The diameter of the powder-core wire is 2mm, and the outer sheath thickness is 0.2mm.

[0022] 2. Substrate pretreatment: The 45 steel substrate is subjected to surface rust removal, degreasing and sandblasting roughening treatment.

[0023] 3. Arc spraying: An arc spraying equipment is used to prepare a coating on the pretreated substrate surface using the aforementioned powder-cored wire. The process parameters for arc spraying are: spraying voltage 28-32V, spraying current 140-160A, spraying distance 90-110mm, and spray gun moving speed 25-35 m / min.

[0024] Preferably, the process parameters for arc spraying are: spraying voltage 30V, spraying current 150A, spraying distance 100mm, and spray gun moving speed 30 m / min.

[0025] 4. Post-coating treatment: After spraying, allow it to cool naturally, and then grind or polish as needed.

[0026] Example 1

[0027] A method for preparing an iron-based amorphous composite coating includes the following steps: 1. Preparation of Powder-Core Wire: A low-carbon steel strip is used as the outer shell, and the interior is precisely filled with a mixed powder core composed of Fe-B-Si-Nb iron-based amorphous alloy powder and Cr3C2 ceramic powder. The Cr3C2 powder accounts for 6% of the total mass. The filled steel strip is processed into a tightly structured continuous powder-core wire through rolling and drawing processes. The diameter of the powder-core wire is 2 mm, and the outer sheath thickness is 0.2 mm. The composition of the Fe-B-Si-Nb iron-based amorphous alloy powder, by mass percentage, includes B 2~8%, Si 2~6%, Nb 2~10%, and the balance Fe and unavoidable impurity elements. The particle size of the Fe-B-Si-Nb iron-based amorphous alloy powder is 5~100 μm; the particle size of the Cr3C2 ceramic powder is 5~100 μm.

[0028] 2. Substrate Treatment and Spraying: 45 steel plate was selected as the substrate, and its surface was roughened and cleaned by sandblasting. Arc spraying equipment was used, employing the aforementioned powder-cored wire. The process parameters for arc spraying were: working voltage 30V, working current 150A, spraying distance 100mm, and spray gun moving speed 30m / min.

[0029] 3. Allow the coated workpiece to cool naturally.

[0030] Example 2

[0031] A method for preparing an iron-based amorphous composite coating includes the following steps: 1. Preparation of Powder-Core Wire: A low-carbon steel strip is used as the outer shell, and the interior is precisely filled with a mixed powder core composed of Fe-B-Si-Nb iron-based amorphous alloy powder and Cr3C2 ceramic powder. The Cr3C2 powder accounts for 5% of the total mass. The filled steel strip is processed into a tightly structured continuous powder-core wire through rolling and drawing processes. The diameter of the powder-core wire is 1.9 mm, and the outer sheath thickness is 0.15 mm. The composition of the Fe-B-Si-Nb iron-based amorphous alloy powder, by mass percentage, includes B 2~8%, Si 2~6%, Nb 2~10%, and the balance Fe and unavoidable impurity elements. The particle size of the Fe-B-Si-Nb iron-based amorphous alloy powder is 5~100 μm; the particle size of the Cr3C2 ceramic powder is 5~100 μm.

[0032] 2. Substrate Treatment and Spraying: 45 steel plate was selected as the substrate, and its surface was roughened and cleaned by sandblasting. An electric arc spraying device was used, employing the aforementioned powder-cored wire. The process parameters for electric arc spraying were: working voltage 28V, working current 140A, spraying distance 90mm, and spray gun moving speed 25m / min.

[0033] 3. Allow the coated workpiece to cool naturally.

[0034] Example 3

[0035] A method for preparing an iron-based amorphous composite coating includes the following steps: 1. Preparation of Powder-Core Wire: A low-carbon steel strip is used as the outer shell, and the interior is precisely filled with a mixed powder core composed of Fe-B-Si-Nb iron-based amorphous alloy powder and Cr3C2 ceramic powder. The Cr3C2 powder accounts for 8% of the total mass. The filled steel strip is processed into a tightly structured continuous powder-core wire through rolling and drawing processes. The diameter of the powder-core wire is 2.1 mm, and the outer sheath thickness is 0.25 mm. The composition of the Fe-B-Si-Nb iron-based amorphous alloy powder, by mass percentage, includes B 2~8%, Si 2~6%, Nb 2~10%, and the balance being Fe and unavoidable impurity elements. The particle size of the Fe-B-Si-Nb iron-based amorphous alloy powder is 5~100 μm; the particle size of the Cr3C2 ceramic powder is 5~100 μm.

[0036] 2. Substrate Treatment and Spraying: 45 steel plate was selected as the substrate, and its surface was roughened and cleaned by sandblasting. Arc spraying equipment was used, employing the aforementioned powder-cored wire. The process parameters for arc spraying were: working voltage 32V, working current 160A, spraying distance 110mm, and spray gun moving speed 35m / min.

[0037] 3. Allow the coated workpiece to cool naturally.

[0038] Comparative Example 1 The overall steps of this comparative example are the same as those of Example 1, except that no Cr3C2 ceramic powder was added in Comparative Example 1, and only Fe-B-Si-Nb iron-based amorphous alloy powder was used to prepare the core wire.

[0039] The composite coatings prepared in Example 1 and Comparative Example 1 are then tested and analyzed: It should be noted that the composite coating prepared in Example 1 is referred to as the FeBSiNb-Cr3C2 coating.

[0040] Microhardness After grinding and polishing, the composite coatings prepared in Example 1 and Comparative Example 1 were tested for hardness along the cross-sectional direction of the coating using an HV-1000 micro Vickers hardness tester.

[0041] Test parameters: Load 200g, loading time 15s.

[0042] Test method: Measure once at 50μm intervals along the cross-section direction, 10 measurements per group, and take the average of the three groups of data.

[0043] Figure 1 The microhardness of the FeBSiNb-Cr3C2 coating along the cross-sectional direction is shown. The average microhardness of the amorphous coating with the ceramic phase reaches 847 HV0.2, and the hardness of the coating with the ceramic phase is significantly higher than that without the ceramic phase. The high microVickers hardness of the coating indicates that it has good wear resistance.

[0044] Porosity In the performance evaluation system of iron-based amorphous coatings, porosity is one of the core indicators for measuring its preparation quality and predicting service reliability. Defects such as pores and microcracks within the coating significantly weaken its density and continuity, not only providing channels for corrosive media intrusion and drastically reducing the coating's corrosion resistance, but also becoming stress concentration points during friction and wear, accelerating crack initiation and propagation, leading to premature coating peeling and failure. Quantitatively characterizing the coating's porosity through metallographic image analysis can directly reflect the spraying process parameters.

[0045] The performance of thermal spray coatings is significantly affected by microstructure. FeBSiNb-Cr3C2 coatings were prepared on 45 steel by arc spraying. The microstructure and structure were characterized by scanning electron microscopy (SEM) and EDS using a ZEISS Sigma 300 microscope (Germany), and the porosity was tested using ImageJ software.

[0046] The results showed that the porosity of the FeBSiNb-Cr3C2 coating was 3.52%, which was significantly lower than the porosity of 8.3% of the FeBSiNb coating without ceramic phase, indicating that Cr3C2 ceramic particles can improve the coating solidification process and enhance its density and overall performance.

[0047] <Amorphous ratio> Amorphous content is a core parameter for evaluating coating structure and performance. It was determined using a D8 X-ray diffractometer (XRD) combined with Bragg's law. Before testing, the samples were ground, polished, and ultrasonically cleaned. A Co target was used, with a scanning angle 2θ ranging from 20° to 100° and a speed of 0.2 ms. By analyzing the intensity and area ratio of the broadened, diffuse peaks of amorphous states to the sharp diffraction peaks of crystalline states in the XRD pattern, the amorphous content can be quantitatively calculated (XRD test results are shown in the figure). Figure 2 This method provides reliable support for optimizing the process parameters of thermal spraying amorphous coatings.

[0048] X-ray diffraction (XRD) is used to measure the amorphous ratio based on the difference in diffraction characteristics between amorphous and crystalline materials: amorphous materials exhibit broadened "bun peaks," while crystalline materials show sharp Bragg diffraction peaks. The ratio is determined by integrating the area (20°-80°, 2θ range) using Jade software for peak fitting, according to formula (1). ,in The integral area of ​​the amorphous scattering peak. The integral area of ​​each crystalline diffraction peak is obtained by peak fitting (after background subtraction) using Jade software.

[0049] The results showed that the amorphous content of the Fe-B-Si-Nb-Cr3C2 coating was 74.21%, lower than that of the Fe-B-Si-Nb coating without Cr3C2 (88.51%). Firstly, Cr3C2, as a hard second phase, occupies a portion of the coating volume fraction, relatively reducing the volume fraction of the continuous Fe-based amorphous matrix. Secondly, during arc spraying, the Cr3C2 ceramic phase may undergo partial decarburization, forming transitional carbide phases such as Cr7C3. Simultaneously, the released Cr and C elements participate in element diffusion and phase transformation during droplet solidification. This structure, where amorphous and crystalline phases coexist, gives the coating both good toughness and excellent wear resistance, enabling it to exhibit good overall performance in harsh environments such as mechanical wear and corrosion.

[0050] <Microstructure> The microstructure of the coating was characterized using a ZEISS Sigma 300 scanning electron microscope (SEM), focusing on the continuity of the amorphous matrix, the dispersion state of the ceramic reinforcing phase, the interfacial bonding, and the distribution of defects such as pores and cracks, providing a structural basis for optimizing coating performance. Due to the absence of grain boundaries and dislocations, the iron-based amorphous coating exhibits significantly higher hardness and strength than traditional steel. Its main wear mechanisms are fatigue wear and oxidation wear, accompanied by a small amount of abrasive wear.

[0051] Introducing a Cr3C2 hard ceramic phase to form a composite coating, Figure 3 The microscopic cross-sectional morphology of the FeBSiNb-Cr3C2 coating and the substrate is shown in Table 1. The spray gun speed during the coating preparation process was 30 m / min. Figure 3 EDS analysis results for regions A, B, C, D, and E in the middle.

[0052] Table 1. EDS analysis results for A, B, C, D, and E

[0053] like Figure 3 The microstructure of regions A, B, C, and D shows relatively similar elemental compositions, close to those of the filament material, primarily consisting of iron-based amorphous phases, but containing some oxygen, indicating oxidation. Oxygen content is particularly high in regions A and D, showing more severe oxidation compared to regions B and D. Region E exhibits extremely high proportions of B, O, and C, especially O, which is significantly higher than in regions A, B, C, and D, while Fe and Cr are extremely low. Image analysis reveals that areas with the same contrast as region E are located near cracks, indicating that this region is a second-phase region rich in B, Nb, and C elements and accompanied by oxygen enrichment, formed during the spraying process, with significant oxidation. Its porosity is 3.52%, significantly better than the 8.3% porosity of the Fe-B-Si-Nb coating without the ceramic phase. Porosity in the coating microstructure is typically formed due to the volume shrinkage of solidified molten particles and the release of gases dissolved in the molten particles. The presence of Cr3C2 allows for tighter particle bonding during coating solidification, thus reducing the formation of gas phase porosity. Furthermore, due to its high hardness, the coating better resists deformation and wear when subjected to external friction, thereby reducing surface defects caused by wear.

[0054] Figure 4Table 2 shows the cross-sectional morphology and overall EDS composition analysis results of the FeBSiNbCr3C2 coating. The main chemical composition of the coating is Fe 49.43, B 27.30, Si 2.55, Nb 1.90, Cl 3.40, Cr 3.28, O 2.13 (at.%). It can be seen that the coating underwent some oxidation during the preparation process.

[0055] Table 2. Elemental content of FeBSiNb-Cr3C2 coating cross-section

[0056] The key to preparing Fe-B-Si-Nb-Cr3C2 amorphous coatings by arc spraying is to achieve microstructural strengthening while ensuring a certain amorphous content through the design of the Fe-B-Si-Nb amorphous matrix and a rapid solidification process. Figure 5 , 6 The elemental surface scan results show that Fe, as the matrix, is distributed in a continuous and dense blue-green color, with no "band-like or cluster-like agglomerations" within the 50 μm observation range, indicating good uniformity and providing a stable matrix for the formation of amorphous state; B is distributed in red diffuse dots with no local enrichment or absence; Si is distributed in green and is mostly uniform; Nb is distributed in purple and is uniformly distributed overall and fully integrated with Fe, B, and Si; Cr (from Cr3C2) is distributed in blue and is uniformly distributed overall with no "large-sized Cr3C2 particle agglomeration enrichment", indicating that Cr element is uniformly distributed in the observation area, indicating that Cr3C2 related elements did not show obvious agglomeration. The alloying elements (Fe, B, Si, Nb) and strengthening phase elements (Cr, C) do not exhibit banded agglomeration along grain boundaries or phase boundaries. Each element is evenly dispersed. Combined with the rapid solidification process of arc spraying, the coating as a whole forms a composite structure dominated by the amorphous phase. However, there are both process and structural defects. The localized high-content areas of O element (yellow) are oxide inclusions formed by the contact between high-temperature molten particles and air. In addition to the components associated with Cr3C2, C element (orange) has sporadic high-content points (low overall proportion and limited impact on the amorphous state). The black areas in the element surface scan (such as in the Fe surface scan) have no element signal, which are porosity defects caused by incomplete fusion of particles or gas residue during spraying (unrelated to element agglomeration). The Cr-C ceramic reinforcing phase introduced by Cr3C2 did not show obvious agglomeration, but existed in a fine and dispersed state. Moreover, the distribution of C and Cr was not strictly "point-to-point" (there were no unmelted coarse Cr3C2 particles). This did not destroy the continuity of the amorphous matrix, but also provided wear-resistant strengthening potential for the coating (which is an important reason why the coating with ceramic phase added has a higher hardness than the coating without ceramic phase added).

[0057] <Friction and Wear Properties> In the quantitative evaluation of wear performance, the wear volume of this coating was measured to be 3.05 × 10⁻⁶. -4 mm 3 The wear rate, calculated using the wear rate formula ΔV / Fvt, is 1.13 × 10⁻⁶. -6 mm 3 / (N・m).

[0058] Cr3C2, as a typical high-hardness ceramic phase (Vickers hardness exceeding 1800 HV), is uniformly distributed in the coating, forming a uniformly distributed ceramic reinforcing phase. Its role is twofold: firstly, Cr3C2 particles themselves possess excellent resistance to plastic deformation, directly withstanding shear stress and compressive loads during friction, reducing direct wear on the amorphous matrix; secondly, Cr3C2 forms a good interfacial bond with the Fe-B-Si-Nb amorphous matrix, preventing premature detachment of the reinforcing phase under friction, thus maintaining the integrity of the coating structure. Furthermore, the compositional uniformity of the amorphous matrix provides stable support for the Cr3C2 particles. The synergistic effect of these two factors allows the coating to maintain a low material loss rate even under long-term friction conditions, exhibiting reliable wear resistance.

[0059] like Figure 7 The wear track width of the Fe-B-Si-Nb coating without Cr3C2 was 241 μm, which is larger than the 229 μm transverse wear area of ​​the Fe-B-Si-Nb-Cr3C2 coating. The former has a wider range of surface material peeling due to abrasive cutting and adhesive wear, while Cr3C2 can enhance local wear resistance and reduce the wear-affected area. In terms of the core wear index, the wear volume of the coating without Cr3C2 was 5.05 × 10⁻⁶. -4 mm 3 (It is a Fe-B-Si-Nb-Cr3C2 coating 3.05×10 -4 mm 3 (1.66 times that of the previous year), with a wear rate of 1.87 × 10⁻⁶. -6 The wear rate of the Fe-B-Si-Nb-Cr3C2 coating decreased to 1.13 × 10 mm3 / (N・m). -6 mm 3 / (N・m), a decrease of about 40%, which confirms that Cr3C2 can reduce the wear of the coating under unit load-unit sliding distance and improve wear resistance efficiency. Mechanistically, coatings without Cr3C2 rely only on the uniformity and basic hardness of the amorphous matrix, which is prone to local plastic deformation and material transfer. However, the wear-resistant reinforcing phase formed by Cr3C2 in the Fe-B-Si-Nb-Cr3C2 coating can transfer friction load, reduce stress concentration in the amorphous matrix and inhibit abrasive cutting, thereby improving performance through dispersion strengthening and matrix synergistic strengthening.

[0060] <Powder Morphology> like Figure 10-12 As shown, the iron-based amorphous wear-resistant coating alloy powder prepared by this invention exhibits an overall irregular blocky / flaky particle morphology. The powder particle size distribution is approximately 5–100 μm, with a relatively uniform particle size distribution, but the particle shape shows obvious angular and broken characteristics.

[0061] These irregular powders have a higher specific surface area and richer surface structure, which is beneficial to improving the mechanical interlocking and bonding strength of the powder in the subsequent thermal spraying process, thus providing favorable conditions for the densification and performance optimization of the coating.

[0062] Figure 13 (a) FeBSiNb iron-based amorphous alloy coating, Figure 13 (b) Transmission electron microscopy image of FeBSiNb-Cr3C2 iron-based amorphous alloy coating. The coating has a high proportion of amorphous phase and the presence of completely amorphous regions can be observed.

[0063] In summary, this invention, through systematic testing and analysis of the obtained coating, revealed that Cr3C2 ceramic particles were dispersed in the matrix using scanning electron microscopy (SEM). X-ray diffraction (XRD) patterns showed typical amorphous dispersed peaks, with a calculated amorphous content of 74.21%. Image analysis revealed a coating porosity of only 3.52%. Vickers hardness testing showed an average cross-sectional microhardness of 847.0 HV0.2. Testing was conducted on a UMT-2 friction and wear testing machine (at room temperature, load 30 N, grinding media Si3N4 balls with a diameter of 6.35 mm, speed 5 mm / s, repeated three times and averaged). The results showed that the coating wear rate was 1.13 × 10⁻⁶. -6 mm 3 The coefficient of friction is stable at a low level of 0.106-0.110 / (N·m). It can be confirmed that by combining the powder core composition of "Fe-B-Si-Nb+6% Cr3C2" with a specific arc spraying process (30V, 150A, 100mm, 30m / min), a high-density, high-hardness and high-wear-resistant iron-based amorphous composite coating can be stably prepared.

[0064] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A Cr3C2 ceramic-reinforced composite powder for arc spraying, characterized in that, It is made by mixing Fe-B-Si-Nb iron-based amorphous alloy powder with Cr3C2 ceramic powder; the mass fraction of Cr3C2 ceramic powder is 5% to 8% based on the total mass of the composite powder.

2. The Cr3C2 ceramic-reinforced composite powder for arc spraying according to claim 1, characterized in that, By mass percentage, Fe-B-Si-Nb iron-based amorphous alloy powder consists of the following components: B 2~8%, Si 2~6%, Nb 2~10%, and the balance Fe and unavoidable impurity elements.

3. The Cr3C2 ceramic-reinforced composite powder for arc spraying according to claim 1, characterized in that, The particle size of Fe-B-Si-Nb iron-based amorphous alloy powder is 5–100 μm; the particle size of Cr3C2 ceramic powder is 5–100 μm.

4. A method for preparing an iron-based amorphous composite coating, characterized in that, Includes the following steps, Low-carbon steel strip is selected as the outer sheath, and Cr3C2 ceramic reinforced composite powder as described in claim 1 is filled into the steel strip. After filling, it is rolled and drawn in sequence to obtain powder core wire. Using powder-core wire as the spraying material, the iron-based amorphous composite coating is obtained by arc spraying on the surface of a metal substrate and then naturally cooling. The process parameters of arc spraying are: spraying voltage 28-32 V, spraying current 140-160 A, spraying distance 90-110 mm, and spray gun moving speed 25-35 m / min.

5. The method for preparing an iron-based amorphous composite coating according to claim 4, characterized in that, The process parameters for arc spraying are: spraying voltage 30V, spraying current 150A, spraying distance 100mm, and spray gun moving speed 30m / min.

6. The method for preparing an iron-based amorphous composite coating according to claim 4, characterized in that, The diameter of the core filament is 1.9~2.1mm, and the thickness of the outer sheath is 0.15-0.25mm.

7. The method for preparing an iron-based amorphous composite coating according to claim 4, characterized in that, The metal matrix is ​​45 steel.

8. The method for preparing an iron-based amorphous composite coating according to claim 4, characterized in that, The metal substrate surface is subjected to rust removal, degreasing, and sandblasting roughening treatment in sequence before being coated with electric arc spray.

9. The method for preparing an iron-based amorphous composite coating according to claim 4, characterized in that, The surface coating of the workpiece, which is cooled naturally, is ground and polished to obtain the iron-based amorphous composite coating.

10. An iron-based amorphous composite coating prepared by the preparation method according to any one of claims 4-9.